2014
DOI: 10.1093/glycob/cwu041
|View full text |Cite
|
Sign up to set email alerts
|

Can an ancestral condition for milk oligosaccharides be determined? Evidence from the Tasmanian echidna (Tachyglossus aculeatus setosus)

Abstract: The monotreme pattern of egg-incubation followed by extended lactation represents the ancestral mammalian reproductive condition, suggesting that monotreme milk may include saccharides of an ancestral type. Saccharides were characterized from milk of the Tasmanian echidna Tachyglossus aculeatus setosus. Oligosaccharides in pooled milk from late lactation were purified by gel filtration and high-performance liquid chromatography using a porous graphitized carbon column and characterized by (1)H NMR spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 76 publications
3
25
0
Order By: Relevance
“…So far, only few studies revealed the significance of O ‐acetylation in OS, limited to acetylated sialic acids, e.g. as found in milk of echidna . O ‐acetylated sialic acids play an important role in human immunology, bacterial and viral infections, and are linked to type I diabetes, rheumatoid arthritis, and autoimmune disorders , processes that HMO and/or breast‐feeding are also associated with .…”
Section: Discussionmentioning
confidence: 99%
“…So far, only few studies revealed the significance of O ‐acetylation in OS, limited to acetylated sialic acids, e.g. as found in milk of echidna . O ‐acetylated sialic acids play an important role in human immunology, bacterial and viral infections, and are linked to type I diabetes, rheumatoid arthritis, and autoimmune disorders , processes that HMO and/or breast‐feeding are also associated with .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, platypuses produce O-acetylated Sia in elevated amounts, a variant of sialic acid shown to interfere with recognition by mammalian and bacterial sialidases. When glycoforms of Tasmanian echidna and platypus milk pools were analyzed [126], the milk oligosaccharides were found to be abundant in C 4 -O-acetylated sialyllactose, such that it comprised the majority of acidic oligosaccharides. Given that sialidase activity is inhibited by C 4 -O-acetylated Neu5Ac [129], the authors suggest that platypuses adopted this defensive strategy to counter-measure pathogenic mediated catabolism.…”
Section: Biological Implications Of C7-9 and C4 O-acetylated Neu5acmentioning
confidence: 99%
“…It is now clear, however, that oligosaccharides rather than lactose predominate in the milks of two of the three major mammalian lineages: monotremes (echidnas and platypus) and marsupials (e.g. koalas, kangaroos and brushtail possums) (Urashima et al 2001(Urashima et al , 2007(Urashima et al , 2013Oftedal et al 2014;Urashima, Fujita, et al 2014). Oligosaccharides are also major constituents in the milks of a variety of eutherians, including elephants, arctoid carnivores (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While early forms of proto-lactation may date back to early synapsids or their tetrapod ancestors in the Carboniferous, >300 million years ago (Oftedal 2013), nipples did not arise until after the divergence of the theriamorph ancestors of eutherians and metatherians (marsupials) from the australosphenidan ancestors of monotremes about 190 million years ago (Luo et al 2011). We recently examined the milk of a monotreme, the Tasmanian echidna (Tachyglossus aculeatus setosus) in an attempt to characterize oligosaccharides that may represent an ancestral state (Oftedal et al 2014). We suggested that the predominant oligosaccharide 4-O-acetyl-3′-sialyllactose (Neu4,5Ac 2 (α2-3)Gal(β1-4)Glc) represented an evolutionary modification of 3′-sialyllactose (Neu5Ac(α2-3)Gal(β1-4)Glc) that served to render this oligosaccharide unavailable to bacterial enzymes (Oftedal et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation